Созидание общественной нормальности в медийном дискурсе: концептуализация и украинская специфика - Кулик, В. (Iнститут соціології НАН України, 2009)
The article analyzes an understudied but important aspect of ideological influence of the media, namely their role in defining beliefs regarding social normality and spreading a normality-oriented worldview. The author conceptually distinguishes normality from normativity: in contrast to the norm as a reflection of certain cultural or ideological values, the normal is of value precisely due to being widespread. The discursive presentation of certain actions or beliefs as normal at the same time constitutes their performers or holders as normal people. The media discourse plays a major role both in defining the limits of normality and in establishing the priority of not transgressing them. The main factors encouraging the audience to perceive media texts in terms of normality rather than norm are, first, plurality and interchangeability of represented objects and, second, the non-problematized nature of representation, that is, the practice of mentioning or showing certain patterns without stressing, discussing or otherwise drawing attention to them. In post-Soviet Ukraine, these factors are particularly active due to political and social contexts in which the media are functioning, and because of ideological orientations of their managers and journalists.